JENIS KELAMIN, ANGKATAN, DAN DURASI DUDUK BERHUBUNGAN DENGAN ANGKA KEJADIAN NYERI PUNGGUNG BAWAH PADA MAHASISWA PROGRAM STUDI SARJANA KEDOKTERAN DAN PROFESI DOKTER FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA SELAMA PELAKSANAAN KULIAH DARING - Alamsyah, Ajib Zaim; Karmaya, I Nyoman Mangku; Wardana, I Nyoman Gede; Widianti, I Gusti Ayu (Universitas Udayana, 2023)
Nowadays in this pandemic era, most of the living sectors are obligated to adapt and conduct their duty from home. However, home environment isn’t always designed as a place to study, unlike campus, which is risky to be unergonomic. Moreover, this condition can result in various musculoskeletal disorders, such as low back pain. The aim of this study is to find out the prevalence of low back pain in Undergraduate Study Program in Medicine and Medical Profession Students of Udayana University during online classes. The design of this research is description with a cross-sectional approach. The research subjects were 468 Undergraduate Study Programs in Medicine and Medical Profession Students of Udayana University. Research data are primary data obtained from the standardized Nordic questionnaire. Students with low back pain is found in a higher proportion, which is 59% compared to not having low back pain which is 41%. Factors that are related towards this condition are sex with the p value = 0.000, batch with the p value = 0.016, and sitting duration with the p value = 0.002.